2018
DOI: 10.1371/journal.pmed.1002597
|View full text |Cite
|
Sign up to set email alerts
|

Chile’s 2014 sugar-sweetened beverage tax and changes in prices and purchases of sugar-sweetened beverages: An observational study in an urban environment

Abstract: BackgroundOn October 1, 2014, the Chilean government modified its previous sugar-sweetened beverage (SSB) tax, increasing the tax rate from 13% to 18% on industrialized beverages with high levels of sugar (H-SSBs) (greater than 6.25 grams [g] sugar/100 milliliters [mL]) and decreasing the tax rate from 13% to 10% on industrialized beverages with low or no sugar (L-SSBs) (less than 6.25 g sugar/100 mL). This study examines changes in beverage prices and household beverage purchases following the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 37 publications
8
118
1
7
Order By: Relevance
“…59,62 Results in this meta-analysis from Mexico were consistent with this. However, a study of a 5% tax in Chile reported significantly greater declines in consumption among the highest SEP groups, 31 and a similar pattern was reported by the second Chile study. 33 The…”
Section: Meta-analyses Of Untaxed Beverage Outcomessupporting
confidence: 65%
“…59,62 Results in this meta-analysis from Mexico were consistent with this. However, a study of a 5% tax in Chile reported significantly greater declines in consumption among the highest SEP groups, 31 and a similar pattern was reported by the second Chile study. 33 The…”
Section: Meta-analyses Of Untaxed Beverage Outcomessupporting
confidence: 65%
“…New evidence, derived from data gathered in Chile and Philadelphia has also emerged considering the effectiveness of SSB's. In one study tax implementation correlated with a 6.4% per capita per month reduction in SSB consumption . In another, SSB's with especially high sugar levels which were taxed at higher rates than ordinary SSB's saw a significant 21.7% per capita reduction when under the effect of the tax .…”
Section: Political Barriers To a Sugar Tax Implementationmentioning
confidence: 93%
“…Mexico saw a 6% reduction in sugar‐sweetened soft drink consumption, with the greatest reduction among households of low socio‐economic status . In Chile, consumption of the higher taxed sugary soft drinks reduced by 21.6% in the year following the implementation of the tax . Notably, very few of these policies targeted confectionary and all limited their scope to sugary drinks.…”
Section: Effectiveness Of Implemented Sugar Taxes In Other Countriesmentioning
confidence: 99%
“…In Chile, a small tax on beverages with greater than 6.25 grams of sugar per 100 milliliters led to accordingly small reductions in purchases of those beverages . Although questions still remain regarding the optimal level of taxation and the amount of reduction that is necessary to significantly improve population health, systematic reviews of the academic literature consistently find that SSB taxes are effective in reducing consumption…”
Section: Sugar‐sweetened Beverage Taxation In Practicementioning
confidence: 99%